Effect of COVID-19 adaptation strategies on arable crop farmers’ output in the Umuahia agricultural zone of Abia State, Nigeria - Udo, Nwaobiala Chioma; Adaku, Ahamefule Blessing; Kelechi, Muojekwu Miracle (International Journal of Sustainable Agricultural Research, 2024)
This study analyzed the effect of COVID-19 adaptation strategies on arable crop farmers’ production in the Umuahia Agricultural Zone of Abia State, Nigeria. A multistage random sampling procedure was used to select seventy-two (72) arable crop farmers. Data for the study were collected through a structured questionnaire and analyzed using both descriptive and inferential statistics (using multiple regression and Z-test analyses). The results showed that arable crop farmers had a high perceived effect (= 2.5) of COVID-19 on arable crop production and a high utilization (= 2.4) of COVID-19 adaptation strategies. The mean farm output of arable crop farmers during and after the COVID-19 pandemic was 2112.871 kg/ha and 23222.282 kg/ha, respectively. Multiple regression analysis revealed that intensive use of organic manure (1.3898 coefficients), family labor (2.0466 coefficients), less cultivable farm land (0.18189 coefficients), and access to government aid (0.6994) all had an impact on the output of arable crop farmers in the study area. The Z-test result showed that there were no significant differences between the farm output of arable crop farmers during the 2112.87109 (SD = 3158.6590) and post-COVID-19 2322.2920 (1032.5310) pandemics. The study concluded that arable crop farmers had high utilization of COVID-19 adaptation strategies. The study therefore recommended the formulation of important policy as Nigeria moves from lockdown aimed at promoting economic recovery and measures to mitigate further spread to promote access of farmers to land, which can lead to increased farmer output in the study area.